Reactive Control of Turbulent Wall-Bounded Flows for Skin Friction Drag Reduction - Stroh, Alexander (KIT Scientific Publishing, 2021)
The work presents an attempt to improve the understanding of reactive drag reducing control of near-wall turbulence with respect to limitations present in a realistic application scenario. The reference reactive control scheme of opposition control is studied using direct numerical simulation through the consideration of various application oriented restrictions, i.e. local control application, limited spatial and temporal resolution of the scheme, sensor noise and control elements arrangement.